Putative salivary protein biomarkers for the diagnosis of oral lichen planus: A case-control study - Buajeeb, W. (BioMed Central Ltd., 2018)
Background: Salivary protein biomarkers for screening and diagnosis of oral lichen planus (OLP) are not well-defined. The objective of this study was to identify putative protein biomarkers for OLP using proteomic approaches. Methods: Pooled unstimulated whole saliva was collected from five OLP patients and five healthy control participants. Saliva samples were then subjected to two-dimensional gel electrophoresis, followed by mass spectrometry to identify putative protein biomarkers. Subsequently, a subset of these putative biomarkers were validated in 24 OLP patients and 24 age-matched healthy control subjects, using an enzyme-linked immunosorbent assay (ELISA). Immunoblotting analyses were then performed in 3 pairs of age- and sex-matched OLP patients and healthy controls to confirm results from the ELISA study. Results: Thirty-one protein spots were identified, corresponding to 20 unique proteins. Notably, fibrinogen fragment D and complement component C3c exhibited increased expression in OLP patients, while cystatin SA exhibited decreased expression in OLP patients, compared with healthy control subjects. ELISA analyses indicated increased expression of fibrinogen fragment D and complement component C3c, and decreased expression of cystatin SA, in the saliva of OLP patients. Statistical differences in the expression of salivary complement C3c were observed between OLP patients and healthy control subjects. Immunoblotting analyses confirmed the results of our ELISA study. Conclusion: Complement C3c, fibrinogen fragment D and cystatin SA may serve as salivary biomarkers for screening and/or diagnosis of OLP. © 2018 The Author(s).